Penggunaan Media Tiga Dimensi Model Kerja pada Pembelajaran IPA di Sekolah Dasar - Desi Dwisetiarezi (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2019)
The implementation of three-dimensional media on science learning in SD Negeri 34 Gantung Ciri has not achieved the optimum result yet. Besides, there were some obstacles which hampering the learning process where teacher was less to involve the students in some learning activities. In addition, the learning setting still was teacher-centered. When it came to science learning, the teacher rarely associated the learning with real situation around students which caused low student learning outcome. Sources of data from this study were the students and the teachers of class V and principals. Data collection techniques were observation, interview, and documentation. The teacher prepared for the Learning Implementation Plan, Student Worksheet and three-dimensional media work model. The use of three-dimensional media work model on the learning of Science Class V in SD Negeri 34 Gantung Ciri could motivate students to be more active and happier with its activities in using three-dimensional media work model. Implementation of learning done by teachers was good. The obstacles that arose in the use of three-dimensional media work model on the learning of Science Class V in the SD Negeri 34 Gantung Ciri were the limitations of the number of three-dimensional media work model used by teachers, limited time on science learning by using three-dimensional media work model.